2019
DOI: 10.1177/1534735419878505
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Electro-Hyperthermia as Palliative Treatment for Pancreatic Cancer: A Retrospective Observational Study on 106 Patients

Abstract: Background: Pancreatic adenocarcinoma has a poor prognosis, resulting in a <10% survival rate at 5 years. Modulated electro-hyperthermia (mEHT) has been increasingly used for pancreatic cancer palliative care and therapy. Objective: To monitor the efficacy and safety of mEHT for the treatment of advanced pancreatic cancer. Methods: We collected data retrospectively on 106 patients affected by stage III-IV pancreatic adenocarcinoma. They were divided into 2 groups: patients who did not receive mEHT (no-mEHT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…Besides many positive case studies being published in a wide range of tumors, several clinical papers analyzing the statistically relevant number of patients have come out recently confirming the added benefits of mEHT treatment to conventional oncotherapy. Combination therapies involving mEHT improved tumor response and survival to radio-chemotherapy in stage III-IV pancreatic cancer patients [ 96 ], the 5-year overall survival of astrocytoma from 24% to 83% compared to the best supportive care alone [ 97 ], the dose-dense temozolomide treatment of recurrent glioblastoma in a cost-effective way [ 98 ], or the local disease-free survival and local disease control in FIGO (International Federation of Gynecology and Obstetrics) stages IIB to IIIB squamous cell carcinoma of the cervix [ 99 ]. This latter phase III randomized controlled trial in advanced cervical cancer showed a high level of clinical evidence on the support of an abscopal effect by mEHT in combination with radio-chemotherapy [ 95 ].…”
Section: Clinical Utilization Of Meht For Upgrading Human Oncothementioning
confidence: 99%
“…Besides many positive case studies being published in a wide range of tumors, several clinical papers analyzing the statistically relevant number of patients have come out recently confirming the added benefits of mEHT treatment to conventional oncotherapy. Combination therapies involving mEHT improved tumor response and survival to radio-chemotherapy in stage III-IV pancreatic cancer patients [ 96 ], the 5-year overall survival of astrocytoma from 24% to 83% compared to the best supportive care alone [ 97 ], the dose-dense temozolomide treatment of recurrent glioblastoma in a cost-effective way [ 98 ], or the local disease-free survival and local disease control in FIGO (International Federation of Gynecology and Obstetrics) stages IIB to IIIB squamous cell carcinoma of the cervix [ 99 ]. This latter phase III randomized controlled trial in advanced cervical cancer showed a high level of clinical evidence on the support of an abscopal effect by mEHT in combination with radio-chemotherapy [ 95 ].…”
Section: Clinical Utilization Of Meht For Upgrading Human Oncothementioning
confidence: 99%
“…In PDAC, an increasing number of clinical studies have demonstrated that different forms of high-fever range hyperthermia including WBH (whole body hyperthermia), HIPEC (hyperthermic intraperitoneal chemotherapy) and locoregional delivery may improve the effects of chemotherapy both concerning survival and quality of life parameters [ 28 , 29 , 30 ]. Recent evidences have also shown the clinical benefits of mEHT (Oncothermia) in PDAC treatment in combination with chemotherapy [ 31 , 32 , 33 ]. These data led to the initiation of clinical trials combining PDAC chemotherapy with locoregional hyperthermia generated by instruments using different radiofrequency and power ranges based either on radiative (70–120 MHz, 800–1500 W, 60 min/treatment) [ 34 ] or capacitive (mEHT: 13.56 MHz, 60–150 W, 60 min/treatment) [ 35 ] delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of mEHT, which has a milder heating effect, as a sensitizer are being demonstrated in studies such as that by Minnaar et al 30 . Modulated electro-hyperthermia has also shown to improve disease management in palliative treatment for brain and pancreatic tumours as a standalone treatment 31,32 . The clinical results showing mEHT has an effect in the absence of higher temperatures prompted the research group to investigate other effects of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical results of mEHT do not match the results observed in vitro. The limited of clinical level 1 evidence should also be noted, however, this is an area which is growing 31,32,35 . Recently, mEHT was investigated in a Phase III randomized controlled trial, as a sensitizer for CCRT for the treatment of local advance cervical cancer (LACC) patients 30 .…”
Section: Discussionmentioning
confidence: 99%